The Correlation between Alcohol Consumption with Anxiety Level on Multiple Drugs User in Sleman - Andrian Fajar Kusumadewi; Carissa Aulia Firliany; Silas Henry Ismanto; Afkar Aulia (HM Publisher, 2020)
Since 2013, data showed alcohol consumption in Indonesia increased from 3% to 3.3%, and 0.8% of the population consumes alcohol over the limit (Riskesdas 2018). Consuming alcohol over the limit not only impacts someone physically but also mentally. One of the mental impacts of alcohol consumption is anxiety. If the anxiety is not treated properly, it can lead a patient to consume more alcohol and, moreover, develop an alcohol addiction. To examine alcohol consumption levels and their correlation to anxiety levels. This study is analytical research with a quantitative cross-sectional survey design. Sampling techniques were done by consecutive sampling with the AUDIT questionnaire survey to measure alcohol consumption level and the T-MAS questionnaire survey to measure anxiety level of respondents. The research sample consists of 30 multiple drug user respondents. We got a 0.569 p-value score with Pearson Chi-Square analysis, which can be interpreted to mean that there is no correlation between alcohol consumption and anxiety level. Patients with alcohol abuse mostly come from low-to-average academic groups, a total of 29 people, and not married groups, a total of 18. There is no correlation between alcohol consumption and anxiety levels. The respondent's anxiety level is influenced by his or her academic grade and marital status.